Leadership as One of the Important Characteristics of Social Activity in Higher Education Students - Kadirov Hasanboy Oribjonovich (International Journal on Integrated Education, 2023)
the article describes the rise of youth leaders in higher education in increasing the social activity of today's young workers and forming competitive leaders